Penguatan Pengetahuan Kader Kesehatan tentang Manajemen Stres sebagai Upaya Promosi Kesehatan di Kecamatan Ciwidey Kabupaten Bandung - Maria Komariah; Ati Surya Mediawati; Theresia Eriyani (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2026)
Unmanaged stress may negatively affect physical and psychological health and reduce quality of life. Community health cadres play a strategic role in community-based health promotion; however, strengthening cadres’ capacity in stress management remains limited. This community engagement program aimed to improve health cadres’ knowledge regarding stress concepts, risk factors, health impacts, and simple stress management strategies in Ciwidey District, Bandung Regency. The program employed participatory education through interactive lectures, discussions, and pretest–posttest evaluation involving 16 health cadres. Educational materials included stress concepts, coping strategies, mindfulness, grounding techniques, and maintaining life balance. Results showed an increase in mean knowledge scores from 61.9±11.8 to 85.0±8.2, with an improvement of 23.1 points, an N-gain of 0.61 (moderate category), and a significant difference based on the Wilcoxon test (p=0.001). Participants also demonstrated active engagement throughout the educational process. These findings suggest that participatory stress management education may strengthen health cadres’ capacity and support community-based health promotion through improved health literacy.